Bad Hijab as a Reaction in Social Acceptance - hasan momeni; abdolhossein kalantari (توسعه اجتماعی, 2016)
Bad Hijabi can survey in many ways be studied. Such as roots and consequences in the fields historical sciences, sociology, psychology, politics sciences and Economics sciences. In this article, we intend to call the Bad Hijabi as a reaction to social acceptance emphasis on social science. Research methodology is survey and it done through questionnaire. Sampling method is targeted. A selected sample is consisting of 300 women over years in Ahvaz city. Among 9 hypotheses, 8 hypotheses were signification correlation with dependent variable. The Regression results show five variables which remain in the modeling explanation about 75 percent of variable dependent variance. Also Equation modeling results confirmed Regression results. Conclusion: “intentionality Bad Hijabi”, in various forms is in replying to social acceptance from Male Others. It denote hajab change in value. Also it moved into from the maintenance character to social acceptance by others.